Distribuição das fontes de infecção do histoplasma capsulatum var: capsulatum em Rio da Prata - Município do Rio de Janeiro (RJ) - Zancopé-Oliveira, Rosely M. (1987)
Histoplasma capsulatum var. capsulatum was isolated from soil of Rio da Prata, a rural area situated near the city of Rio de Janeiro. Analysis of 111 soil samples determined 8 (7.2%) contaminated foci, all of them related to chicken habitats. One infected site was enriched with both chicken and bat guano. The high frequency of isolation of the fungus from the soil in this region is similar to that observed in the endemic areas of the USA.